Keunikan Dan Kearifan Lokal Alun-Alun Suryakencana Sebagai Pendapatan Wisata Di Taman Nasional Gunung Gede Pangrango (TNGGP) - Yuri Rahayu; Yulianto; Saeful Bahri (Journal of Tourism and Economic, 2019)
Local wisdom is the protection, environmental management in the effort to preserve and preserve the original culture and environment by using the common sense of the people (cognition) in shaping the social institution among local and surrounding residents who sometimes Neglected even in the damaged by humans. In fact, local wisdom can be a proof of history that can be preserved. The research methods used are qualitative researchers. Research that obtained data not "as it should be", but based on as it is happening in the field, experienced, perceived and thought by participants aiming to understand a phenomenon in social contexts The process of deep communication interaction between researchers and the phenomenon studied. The sample used is purposive sampling. The uniqueness of Suryakencana Square is that it has a large and beautiful grass field that can accommodate thousands of climbers, have springs that are rarely encountered in other camps that make it easy for climbers to fulfill their camping activities. The beautiful Edelwess flower expanse and included one of edelwiess species rarely found in other mountains is one of the tourist magnets for climbers to return to the area and Spot suitable for beginners as a medium Warming up to do fantasy climbing. Cash flows due to a transaski of ticket purchase from prospective climbers as cons of performance in the service provided to the management of TNGGP in a particular period it is a revenue that can be allocated to Development and maintenance of the TNGGP region and as one of the contributions to the State and local Treasury for the welfare of the surrounding.